An Impact Study of Food Product Packaging on Consumer Buying Behaviour: A Study Premise to Himachal Pradesh-India - Thakur, Pankaj; Mehta, Piyush; Gupta, Nikhil (International Journal of Bio-resource and Stress Management, 2017)
Packaging is the prime force to provide information to the consumer and should satisfy legal requirements for product identification, nutritional value, ingredient declaration, net weight, and manufacturer information. A package is the face of a product and often is the only product exposure consumers experience prior to purchase. Consequently, distinctive or innovative packaging can boost sales in a competitive environment. The concerned study has analyzed the consumer buying behaviour of food packaging product and has examined the customer preference to buy different food products. It has also analyzed the reasons of customer preferences over the commonly preferred food product brands in the market. The present investigation was carried out with 100 respondents from Mandi District of Himachal Pradesh. Convenience sampling technique was used for the present study for collection of data. The study was conducted by using both Primary and Secondary data. A structured questionnaire was prepared for the present study. The primary data for the present study was collected with the help of questionnaire. The secondary data for the present study was collected from journals, magazines, research articles, newspapers, and website. Findings revealed that the impact of packaging and its elements on consumer’s purchase decision is quite significant in respect to the consumer’s varied choice. For this purpose, the Package’s elements were identified on the basis of its graphics quality, color, size, form, and material of packaging being used on the product.